Magnitude and Kinetics of T Cell and Antibody Responses During H1N1pdm09 Infection in Inbred Babraham Pigs and Outbred Pigs - Edmans, Matthew; McNee, Adam; Porter, Emily; Vatzia, Eleni; Paudyal, Basu; Martini, Veronica; Gubbins, Simon; Francis, Ore; Harley, Ross; Thomas, Amy; Burt, Rachel; Morgan, Sophie; et al. (Frontiers in Immunology, 2021)
We have used the pig, a large natural host animal for influenza with many physiological similarities to humans, to characterize alpha-beta, gamma-delta T cell and antibody (Ab) immune responses to the 2009 pandemic H1N1 virus infection. We evaluated the kinetic of virus infection and associated response in inbred Babraham pigs with identical MHC (Swine Leucocyte Antigen) and compared them to commercial outbred animals. High level of nasal virus shedding continued up to day 4-5 post infection followed by a steep decline and clearance of virus by day 9. Adaptive T cell and Ab responses were detectable from day 5-6 post infection reaching a peak at 9-14 days. Gamma-delta cells produced cytokines ex vivo at day 2 post infection, while virus specific IFN-gamma producing gamma-delta T cells were detected from day 7 post infection. Analysis of NP tetramer specific and virus specific CD8 and CD4 T cells in blood, lung, lung draining lymph nodes and broncho-alveolar lavage (BAL) showed clear differences in cytokine production between these tissues. BAL contained the most highly activated CD8, CD4 and gamma-delta cells producing large amounts of cytokines, which likely contribute to elimination of virus. The weak response in blood did not reflect the powerful local lung immune responses. The immune response in the Babraham pig following H1N1pdm09 influenza infection was comparable to that of outbred animals. The ability to utilize these two swine models together will provide unparalleled power to analyse immune responses to influenza.